12 minute consultation: an evidence‐based approach to the management of a child with speech and language delay. (12th April 2013) - Lawrence, R.; Bateman, N.
Abstract Background Speech and language delay is a common developmental disorder. Persistent delay may lead to adverse effects on literacy, educational achievement and psychosocial development. Affected children are commonly referred to the otolaryngologist; hence, a structured management approach is required to facilitate diagnosis and allow for early intervention and improved outcomes. Methods A literature search was performed on 05 November 2012 using the MEDLINE, EMBASE and Cochrane databases with the search terms paediatric, children, speech, language, delay, disorder, investigation and management. Relevant references from selected articles were reviewed after reading the abstract. Results Speech and language delay may be primary, meaning there is no associated comorbidity to account for the delay, or secondary, where it can be attributed to another condition or syndrome. Secondary causes include hearing loss and syndromes such as Down syndrome amongst many others. Speech and language therapy has been shown to be effective for primary disorders. If the delay is found to be secondary in nature, onward referral to an appropriate healthcare professional is required. Conclusions The outpatient consultation for a child with speech and language delay should consist of a structured history and examination with the aim of identifying whether the delay is primary or secondary in nature. Relevant targeted investigations should lead to a correct diagnosis of the delay and enable appropriate treatment. This often requires a multidisciplinary approach and always requires full cooperation from the child's parents.